MitraClip Treatment of Secondary Mitral Regurgitation in Heart Failure with Reduced Ejection Fraction: Lessons and Implications from Trials and Registries. Issue 4 (3rd July 2020) - Godino, Cosmo; Munafò, Andrea; Sisinni, Antonio; Margonato, Alberto; Saia, Francesco; Montorfano, Matteo; Agricola, Eustachio; Alfieri, Ottavio; Colombo, Antonio; Senni, Michele
ABSTRACT: Transcatheter mitral valve intervention using the MitraClip system has evolved as a new tool for the treatment of secondary mitral regurgitation (SMR) in patients with heart failure and reduced left ventricular ejection fraction (HFrEF). The purposes of this paper are, first, to review the pathophysiological mechanisms underlying the onset of SMR within the context of HFrEF progression; secondly, to reconcile the results from MitraClip randomized clinical trials and "real-world" registries, in order to highlight in a patient-based strategy the most relevant clinical predictors of favorable outcome after MitraClip implantation. The final goal is to identify the phenotype of the "ideal" patient and the most favorable timing for MitraClip treatment of SMR within the broad spectrum of HFrEF presentation.Guest Editor